Cetacean Strandings From Space: Challenges and Opportunities of Very High Resolution Satellites for the Remote Monitoring of Cetacean Mass Strandings - Penny J. Clarke; Penny J. Clarke; Hannah C. Cubaynes; Karen A. Stockin; Karen A. Stockin; Carlos Olavarría; Asha de Vos; Asha de Vos; Peter T. Fretwell; Jennifer A. Jackson (Frontiers in Marine Science, 2021)
The study of cetacean strandings was globally recognised as a priority topic at the 2019 World Marine Mammal Conference, in recognition of its importance for understanding the threats to cetacean communities and, more broadly, the threats to ecosystem and human health. Rising multifaceted anthropogenic and environmental threats across the globe, as well as whale population recovery from exploitation in some areas, are likely to coincide with an increase in reported strandings. However, the current methods to monitor strandings are inherently biased towards populated coastlines, highlighting the need for additional surveying tools in remote regions. Very High Resolution (VHR) satellite imagery offers the prospect of upscaling monitoring of mass strandings in minimally populated/unpopulated and inaccessible areas, over broad spatial and temporal scales, supporting and informing intervention on the ground, and can be used to retrospectively analyse historical stranding events. Here we (1) compile global strandings information to identify the current data gaps; (2) discuss the opportunities and challenges of using VHR satellite imagery to monitor strandings using the case study of the largest known baleen whale mass stranding event (3) consider where satellites hold the greatest potential for monitoring strandings remotely and; (4) outline a roadmap for satellite monitoring. To utilise this platform to monitor mass strandings over global scales, considerable technical, practical and environmental challenges need to be addressed and there needs to be inclusivity in opportunity from the onset, through knowledge sharing and equality of access to imagery.